Pengaruh Mutasi Kerja dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan BPJS Ketenagakerjaan Karimunjawa Surabaya - Ariza Rahmawati; Mei Retno Adiwati (Universitas Islam Nahdlatul Ulama Jepara, 2021)
Employees want to be treated appropriately and properly as human resources. Employees need to attend to things that support job satisfaction, such as the work environment, tasks, job transfers, and more. This study aims to determine the impact of job increase and work environments on BPJS Ketenagakerjaan Brim Karimunjawa Surabaya’s job satisfaction. Quantitative methods used in this study. The population and sample of this study were staffed by BPJS Ketenagakerjaan Brim Karimunjawa Surabaya. Partial least squares (PLS) is used to test the hypothesis of this study using SmartPLS. The consequences of this research concluded that the increase in employment has had a positive and insignificant effect on job satisfaction and that the employment environment has had a positive and significant impact on employee job satisfaction. Work experience increase with a job transfer. Increasing work experience increases the knowledge and skills that employees have at work. The work environment makes a significant contribution to job satisfaction, the better the work environment in the company, the better the job satisfaction of employees.